Multilevel Analyses of School and Children's Characteristics Associated With Physical Activity. (October 2014) - Gomes, Thayse Natacha; dos Santos, Fernanda K.; Zhu, Weimo; Eisenmann, Joey; Maia, José A. R.
ABSTRACT BACKGROUND Children spend most of their awake time at school, and it is important to identify individual and school‐level correlates of their physical activity (PA) levels. This study aimed to identify the between‐school variability in Portuguese children PA and to investigate student and school PA correlates using multilevel modeling. METHODS The sample included 1075 Portuguese children of both sexes, aged 6‐10 years, from 24 schools. Height and weight were measured and body mass index (BMI) was estimated. Physical activity was estimated using the Godin and Shephard questionnaire (total PA score was used); cardiorespiratory fitness was estimated with the 1‐mile run/walk test. A structured inventory was used to access information about the school environment. A multilevel analysis (level‐1: student‐level; level‐2: school‐level) was used. RESULTS Student‐level variables (age, sex, 1‐mile run/walk test) explained 7% of the 64% variance fraction of the individual‐level PA; however, school context explained approximately 36% of the total PA variance. Variables included in the model (school size, school setting, playground area, frequency and duration of physical education class, and qualification of physical education teacher) are responsible for 80% of the context variance. CONCLUSIONS School environment is an important correlate of PA among children, enhancing children's opportunities for being active and healthy.